2009
DOI: 10.1007/s11104-009-0141-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of the rice ionome in leaves and grain: identification of QTLs for 17 elements including arsenic, cadmium, iron and selenium

Abstract: Research into the composition of cereal grains is motivated by increased interest in food quality. Here multi-element analysis is conducted on leaves and grain of the Bala x Azucena rice mapping population grown in the field. Quantitative trait loci (QTLs) for the concentration of 17 elements were detected, revealing 36 QTLs for leaves and 41 for grains. Epistasis was detected for most elements. There was very little correlation between leaf and grain element concentrations. For selenium, lead, phosphorus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
204
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(230 citation statements)
references
References 32 publications
21
204
5
Order By: Relevance
“…Although, substantial genetic diversity for mineral content has been observed in rice, but linkage mapping of genes/QTLs for iron and zinc contents has gained momentum recently (Stangoulis et al 2007;Garcia-Oliveira et al 2009;Norton et al 2010). Notably, out of eight putative QTLs for iron content identified in this study, seven were from "Palman 579" with six QTLs present on three chromosomes (chromosomes 2, 10 and 12).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Although, substantial genetic diversity for mineral content has been observed in rice, but linkage mapping of genes/QTLs for iron and zinc contents has gained momentum recently (Stangoulis et al 2007;Garcia-Oliveira et al 2009;Norton et al 2010). Notably, out of eight putative QTLs for iron content identified in this study, seven were from "Palman 579" with six QTLs present on three chromosomes (chromosomes 2, 10 and 12).…”
Section: Discussionmentioning
confidence: 77%
“…But only a few studies on linkage mapping of QTLs for mineral content in rice (Garcia-Oliveira et al 2009;Norton et al 2010;Stangoulis et al 2007) have been reported. In this paper, we report the field evaluation of a F 2 population derived from the cross between "PAU201" (high yielding) and "Palman 579" (iron-rich) varieties of indica rice for yield and yield attributes.…”
Section: Introductionmentioning
confidence: 99%
“…We obtained moderate heritability (greater than 30%) for several elements, including Mg, phosphorus (P), sulfur (S), potassium (K), Ca, Mn, Fe, Co, Zn, strontium (Sr), and molybdenum (Mo). Low heritabilities were reported previously for seed accumulation of aluminum (Al) and As (Norton et al, 2010) as well as for Se, Na, Al, and rubidium (Rb) in a similarly designed study in maize seed kernels . The relatively lower heritabilities for these elements, including boron (B), Cd, and Se, could be explained by environmental differences between the experiments, element accumulation near the limit of detection via ICP-MS, and the absence of genetic variation affecting the concentrations of these elements.…”
Section: Phenotypic Diversity For Seed Element Concentrations In Thementioning
confidence: 73%
“…This diverse collection of sorghum germplasm contains genetic variation with undiscovered impact on seed element composition (Das et al, 1997). Mapping quantitative trait loci for seed element concentration has been successful in a number of species, including Arabidopsis (Arabidopsis thaliana; Vreugdenhil et al, 2004;Waters and Grusak, 2008;Buescher et al, 2010), rice (Oryza sativa; Norton et al, 2010;Zhang et al, 2014), wheat (Triticum aestivum; Shi et al, 2008;Peleg et al, 2009), and maize (Zea mays; Simic et al, 2012;Baxter et al, 2013Baxter et al, , 2014. Genome-wide association (GWA) mapping is well suited for uncovering the genetic basis for complex traits, including seed element accumulation.…”
mentioning
confidence: 99%
“…Evidence from mapping of quantitative trait loci (QTL) has identified a region on chromosome 8 of rice, that is responsible for increasing shoot P concentration and decreasing grain As concentration (38). Additionally, in a different rice mapping population, a region on chromosome 5 has been identified as increasing shoot P concentration and deceasing shoot As concentration (39). These relationships at the genetic level indicate that there is a relationship between P and As.…”
Section: Discussionmentioning
confidence: 99%